Regulation and Function of the Peg3 Imprinted Domain - Hongzhi He; Joomyeong Kim (Genomics & Informatics)
A subset of mammalian genes differ functionally between two alleles due to genomic imprinting, and seven such genes (Peg3, Usp29, APeg3, Zfp264, Zim1, Zim2, Zim3) are localized within the 500-kb genomic interval of the human and mouse genomes, constituting the Peg3 imprinted domain. This Peg3 domain shares several features with the other imprinted domains, including an evolutionarily conserved domain structure, along with transcriptional co-regulation through shared cis regulatory elements, as well as functional roles in controlling fetal growth rates and maternal-caring behaviors. The Peg3 domain also displays some unique features, including YY1-mediated regulation of transcription and imprinting; conversion and adaptation of several protein-coding members as ncRNA genes during evolution; and its close connection to human cancers through the potential tumor suppressor functions of Peg3 and Usp29. In this review, we summarize and discuss these features of the Peg3 domain.